Impact of suspension of orthodontic care on patients’ quality of life (Research, Society and Development, 2022)
We aimed to investigate the impact of the suspension of orthodontic care during the Covid-19 pandemic on patients' anxiety, treatment, and quality of life. This is a cross-sectional study conducted from data collected by an online questionnaire on Google Forms. A total of 65 questionnaires were evaluated, 37 from patients over 18 years old (adult group) and 28 from those responsible for patients under 18 years old (children/adolescents group). The questionnaire contained 27 questions, which addressed anxiety about the pandemic and treatment after discontinued care, and the impact of oral problems on quality of life (OHIP-14). According to the anxiety scale, adults were more anxious than children/adolescents about the pandemic (p=0.033). Adults showed a greater need for urgent care (p=0.002) or maintenance of treatment (p=0.040) than children/adolescents, and in both, private care was more sought after than public care (p=0.038). Speech problems (p=0.043) and severe pain (p=0.050) were more frequent in children/adolescents than in adults. Children/adolescents more often reported that life in general was made worse because of problems with their teeth, mouth, or braces, compared to adults (p=0.047). We concluded that adults and children/adolescents were anxious about the impacts of missed appointments during the Covid-19 pandemic on orthodontic treatment. The quality of life of the patients was affected by the suspension of care and was more relevant among children/adolescents.